Hawaii - Townsend, Helen, ....- (London : Dorling Kindersley, 2017)
The ideal travel companion, full of insider advice on what to see and do, plus detailed itineraries and comprehensive maps for exploring the beautiful islands of Hawaii. Snorkel among tropical fish in Hanauma Bay, relax on the idyllic North Shore's gorgeous Pu'upoa Beach or explore Hawaii Volcanoes National Park: everything you need to know is clearly laid out within colour-coded chapters. Discover the best of Hawaii with this indispensable travel guide. Inside DK Eyewitness Travel Guide Hawaii: - Over 15 colour maps help you navigate with ease - Simple layout makes it easy to find the information you need - Comprehensive tours and itineraries of Hawaii, designed for every interest and budget - Illustrations and area plans show in detail Waikiki beachfront, Bishop Museum, Haleakala National Park, Hawaii Volcanoes National Park and more - Colour photographs of Hawaii's beautiful beaches, breathtaking national parks, stunning coastline, harbour towns and more - Detailed chapters, with area maps, cover Honolulu, Waikiki, O'ahu, Moloka'i and Lana'i, Maui, Hawai'i Island and Kaua'i - Historical and cultural context gives you a richer travel experience: learn about the formation of the Hawaiian Islands and its flora, fauna and marine life; oral tradition and literary connections; hula and Hawaiian music; traditional Hawaiian crafts; surfing, scuba diving and snorkeling scene; traditional food and drink, including Kona coffee; and festivals and events.
Keywords: Reidsgids ; Hawaii; Reisgids ; Verenigde Staten